Numerical Analysis of Double Diffusive Laminar Natural Convection in a Right Angle Triangular Solar Collector - Mahdi, Jasim M.; Rasham, Ali M.; Thamir H. Ali, Thamir H. Ali H. (Al-Khwarizmi Engineering Journal, 2013)
A numerical study of the double-diffusive laminar natural convection in a right triangular solar collector has been investigated in present work. The base (absorber) and glass cover of the collector are isothermal and isoconcentration surfaces, while the vertical wall is considered adiabatic and impermeable. Both aiding and opposing buoyancy forces have been studied. Governing equations in vorticity-stream function form are discretized via finite-difference method and are solved numerically by iterative successive under relaxation (SUR) technique. Computer code for MATLAB software has been developed and written to solve mathematical model. Results in the form of streamlines, isotherms, isoconcentration, average Nusselt, and average Sherwood number, are presented for wide range of the buoyancy ratio , angle of inclined glass cover with horizontal coordinate , Lewis number , thermal Rayleigh number , and Prandtl number . The results show that above parameters have strong influences on the patterns of streamline, isotherms, isoconcentration, average Nusselt number and average Sherwood number. Results show that a decrease in the angle of inclined glass cover with horizontal coordinate (  leads to increase average Nusselt number and average Sherwood number. For (N > 0), both average Nusselt number and average Sherwood number increase with increasing of buoyancy ratio and Rayleigh number. By contrast for (  these values decreases. Also, increasing of the buoyancy ratio for positive (N > 0), at the same Rayleigh number enhance the heat and mass transfer rate. A comparison is made with the previous numerical results and it found to be reveal a good agreement.